Italian military-humanitarian operation “Mare Nostrum” (2013-2014) - Vira Savaryn (Європейські історичні студії, 2018)
The article touches upon the policy of Italy in regulating the situation in the Mediterranean Sea area, in particular, the military-humanitarian operation “Mare Nostrum” (“Our Sea”) has considered in details. The preconditions of the crisis situation near the banks of Lampedusa Island in the context of the Italian-Libyan relations have been investigated.